2021
DOI: 10.1097/md.0000000000027275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between remifentanil and other opioids in adult critically ill patients

Abstract: Background and aims: To identify the efficacy and safety of remifentanil when compared with other opioids in adult critically ill patients. Methods: We searched for studies in the Cochrane Library, MEDLINE, and EMBASE that had been published up to May 31st, 2019. Randomized clinical trials using remifentanil comparing with other opioids for analgesia were included. Two reviewers independently applied eligibility criteria, assessed quality, and extracted data. Duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
9
2
2
Order By: Relevance
“…The results are broadly consistent with previous single-center studies from other countries that compared remifentanil to fentanyl, which have shown that remifentanil may be associated with shorter duration of mechanical ventilation, length of stay, and lower incidence of delirium. 26 , 29 , 30 , [36] , [37] , [38] , [39] , [40] , [41] , [42] However, our study has the largest sample size with a variable case-mix from a general ICU. Since it is the first study to be conducted in Australia, the results may be particularly relevant to Australian-New Zealand practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are broadly consistent with previous single-center studies from other countries that compared remifentanil to fentanyl, which have shown that remifentanil may be associated with shorter duration of mechanical ventilation, length of stay, and lower incidence of delirium. 26 , 29 , 30 , [36] , [37] , [38] , [39] , [40] , [41] , [42] However, our study has the largest sample size with a variable case-mix from a general ICU. Since it is the first study to be conducted in Australia, the results may be particularly relevant to Australian-New Zealand practice.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 11 In contrast, remifentanil is an ultra-short-acting opioid with a short context-sensitive half-life of 3–4 min. [22] , [23] , [24] , [25] , [26] , [27] Although clinical trials, systematic reviews, and meta-analyses have shown that the use of remifentanil may be associated with a reduction in the duration of mechanical ventilation and ICU length of stay, [28] , [29] , [30] its use in Australian ICUs is infrequent or rare. 31 While the reasons for this have not been explored, possible reasons could be attributed to the high cost of remifentanil until recently 7 and to the relative unfamiliarity with its use by intensivists with limited exposure to anaesthetic practice.…”
Section: Introductionmentioning
confidence: 99%
“…Remifentanil is the opioid most consistently associated with the development of opioid-induced hyperalgesia (OIH) [38], a condition that must be distinguished from acute opioid withdrawal, and which presents particularly where opioid drugs have been used at high dosages over long time periods with an especially elevated incidence in younger patients. This condition may require the use of additional analgesics, and as a result may prolong the time spent on mechanical ventilation.…”
Section: Analgesic Agentsmentioning
confidence: 99%
“…▴ Remifentanil has single pharmacokinetic and pharmacodynamic profiles. Unfortunately, it is expensive compared to other conventional opioids ( 33 ). Current literature has demonstrated that an infusion of lidocaine effectively treats acute perioperative pain and various circumstances of chronic pain in pediatrics, particularly pain refractory to conventional regimens ( 34 , 35 ).…”
Section: Dose Optimization Strategiesmentioning
confidence: 99%